Some properties associated with hermite matrix polynomials - Altin, Charles A.; Çekim, Bayram (My University, 2012)
The main object of this paper is to give a different approach to proof of bilinear generating function and obtain finite summations for the Hermite matrix polynomials. Also linearization of products of Hermite matrix polynomials is given. The relations between Hermyte and Gegenbauer matrix polynomials in this study are indicated.
Keywords: Bilinear generating function; Finite summation; Gegenbauer matrix polynomials; Hermite matrix polynomials